SPACE SECURITY SYSTEM USING INFRA RED TECHNOLOGY - Agus Triyono; Luyung Dinaini, SKom, MMSI (Jurnal Sistem Komputer, 2004)
By leveraging existing technology and at this point, these tools can we design asmaller and simpler, without reducing the reliability of these tools. In the design ofthis tool there is a little weakness, namely in the operation of this tool basically,because of the quality factor of the quality of each of the different components of thestandardization of a component. Therefore, space security system using infraredtechnology needed to develop its presence.